2021
DOI: 10.21037/atm-20-7730
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of the management of a relapsed clubfoot

Abstract: The management of idiopathic clubfoot has transformed over the past several decades as the Ponseti method for the correction of this deformity became the standard of care, and surgical release has almost all but been abandoned. The Ponseti method has shown very high initial success rate and excellent long-term functional results. Relapse of the deformity, however, continues to be a major problem, occurring in up to 40% of patient, and there is no consensus on the definition and management of the relapsed clubf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This conservative method significantly reduces the complications of the extended surgery, such as stiffness and arthritis of the foot in adulthood. Previous studies reported relapse rates up to 40% [ 9 ]. However, a common question that is usually raised is, “What factors are associated with relapse?” This study analyzed a combination of clinical factors for their association with relapse after treatment with the Ponseti method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conservative method significantly reduces the complications of the extended surgery, such as stiffness and arthritis of the foot in adulthood. Previous studies reported relapse rates up to 40% [ 9 ]. However, a common question that is usually raised is, “What factors are associated with relapse?” This study analyzed a combination of clinical factors for their association with relapse after treatment with the Ponseti method.…”
Section: Discussionmentioning
confidence: 99%
“…However, relapses are common in severe clubfeet and are probably caused by the same pathology that initiated the deformity. The rate of recurrence after using the Ponseti method, occurring in up to 40% of patient [ 9 ]. The factors that relate to the recurrence are still debatable [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported relapse rates of up to 40% [33]. However, a common question that is usually raised is, "What factors are associated with relapse?"…”
Section: Discussionmentioning
confidence: 99%
“…The physiopathology of forefoot adduction attributes to the imbalance between the elongated lateral column and shortened medial column of the midfoot. Hence many types of osteotomies have been attempted which require internal or external fixation and restricted weight bearing 10 , 11 , 12 , 13 , 14 . However, the bony deformity in children could also be corrected by manipulating the growth behavior of an open physis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the deformities, residual forefoot adduction with supination after treatment is a common issue which is also referred to as the “bean‐shaped foot” 9 . To the best of our knowledge, the combination of a cuboid closing with a cuneiform opening wedge osteotomy or with a trans‐midfoot osteotomy is currently the most popular procedure to correct the residual forefoot adduction 10 , 11 , 12 , 13 , 14 . However, complications such as neurovascular lesion, non‐union or permanent foot stiffness might occur during the operation.…”
Section: Introductionmentioning
confidence: 99%